Multi-intelligence-based literacy learning training to improve teacher pedagogic competence - Sholeh, Khabib; Kadaryati, Kadaryati; Faizah, Umi; Wahyono, Hari (Universitas Muhammadiyah Magelang, 2021)
This community service activity was carried out at SD Sukomanah, Purwodadi District, Purworejo Regency. The activity was carried out by involving 30 elementary school teachers in Purwodadi, Purworejo, with the aim of improving the pedagogic abilities of teachers in empowering lifelong learners through literacy learning based on multiple intelligences. The methods used in service activities are socialization, simulation, monitoring and evaluation. Most of the participants have understood and three participants have even practiced multiple intelligence-based literacy learning for lifelong learners.